2001
DOI: 10.1291/hypres.24.501
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensinogen Gene Polymorphism with Erythropoietin-Induced Hypertension: A Preliminary Report.

Abstract: The association of the angiotensinogen (AGT) gene variation at codon 235, the T235 variant, with hypertension induced by erythropoietin (Epo) was investigated in patients with progressive renal disease requiring treatment for renal anemia with Epo. The subjects for the study were patients with renal diseases with serum creatinine concentration exceeding 2 mg/dl and a hematocrit (Ht) of less than 30%. During the run-in period, blood pressure was well controlled with an appropriate salt restricted diet and/or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…[37][38][39][40][41][42][43][44][45][46][47] Nevertheless, Epo has potentially beneficial effects on the endothelial and neuroprotection, maybe via antiapoptosis. 48 -51 In our previous study, we demonstrated that the Epo receptor exists in various progenitor cell surfaces and tissues.…”
Section: Lee Et Al Epo-bp and Blood Pressure 443mentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47] Nevertheless, Epo has potentially beneficial effects on the endothelial and neuroprotection, maybe via antiapoptosis. 48 -51 In our previous study, we demonstrated that the Epo receptor exists in various progenitor cell surfaces and tissues.…”
Section: Lee Et Al Epo-bp and Blood Pressure 443mentioning
confidence: 99%
“…It has also been reported that patients with a family history and past history of hypertension tend to have hypertension because of the presence of risk for the disease [180]. A relationship between the inherited factors for hypertension and the T allele of M235T angiotensinogen gene polymorphism has also been reported [181].…”
Section: Rationale Hypertensionmentioning
confidence: 96%
“…A previous study found that EPO can ameliorate anemia, inhibit inflammatory reactions, promote the growth of blood vessels, inhibit apoptosis, and reduce the expression of cytokines and inflammatory factors, thereby protecting organs from damage (30). In recent years, a large number of animal experiments have shown that EPO can delay the progress of chronic kidney disease and improve the degree of interstitial fibrosis, and has a certain renal protective effect (31)(32)(33). A study conducted by Nakazawa et al demonstrated that EPO is able to inhibit renal tubule cell apoptosis, thereby reducing the degree of renal interstitial fibrosis (34).…”
Section: Discussionmentioning
confidence: 99%